Disproportionately Disenfranchised: Gendered Impacts of Interference in Collective Bargaining in Canada - Rollmann, Hans (Just Labour, 2011)
Much has written about the growth of legislative in terference in collective bargaining and the right to strike in Canada in the latter part of the 20th century. However, consideration of the specifically gendered impacts of this interference has been largely neglected. This paper argues that suspension of collective bargaining rights and the right to strike impacts women workers in unique and disproportionate ways. Two cursory case studies from Ontario and Newfoundland and Labrador provide examples of how suspension of bargaining rights has a differential impact on women. The paper calls attention to the need for a heightened focus on the specifically gendered impacts of neoliberal governments’ growing propensity to suspend collective bargaining rights in Canada.